The paradoxical role of MDSCs in inflammatory bowel diseases: From bench to bedside - Zhao, Fan; Gong, Wenbin; Song, Jiaojiao; Shen, Zhe; Cui, Dawei (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a group of bone marrow derived heterogeneous cells, which is known for their immunosuppressive function especially in tumors. Recently, MDSCs have receiving increasing attention in pathological conditions like infection, inflammation and autoimmune diseases. Inflammatory bowel diseases (IBD) are a series of immune-dysfunctional autoimmune diseases characterized by relapsing intestinal inflammation. The role of MDSCs in IBD remains controversial. Although most studies in vitro demonstrated its anti-inflammatory effects by inhibiting the proliferation and function of T cells, it was reported that MDSCs failed to relieve inflammation but even promoted inflammatory responses in experimental IBD. Here we summarize recent insights into the role of MDSCs in the development of IBD and the potential of MDSCs-targeted therapy.